Analysis of the Effectiveness of AI Learning Systems in Facilitating Interactive Learning in Junior High Schools - Jihan Hidayah Putri; Israq Maharani (PT ARRUS Intelektual Indonesia, 2023)
This research aims to analyze the effectiveness of the AI ​​(Artificial Intelligence) learning system in facilitating interactive learning in junior high schools. In this research, the design that will be used is quantitative research. The research method used is quasi-experiment with a design of two groups of cases and controls. Research location at SMP Negeri 1 Beringin, Beringin District, Deli Serdang Regency, North Sumatra Province. The research results show that the use of AI learning systems in interactive learning in junior high schools has significant effectiveness. AI learning systems are able to provide a more interesting and interactive learning experience for students, as well as encouraging active participation in the learning process. Additionally, AI learning systems also provide fast and accurate feedback to students, allowing them to improve their understanding and performance immediately. However, this research also found several factors that need to be considered in implementing AI learning systems in junior high schools. These factors include the availability of adequate technological infrastructure, adequate teacher training in using AI learning systems, as well as strong support from the school and related stakeholders. In conclusion, this research shows that AI learning systems have the potential to increase the effectiveness of interactive learning in junior high schools. However, successful implementation requires cooperation between schools, teachers, students and related stakeholders. It is hoped that the results of this research can become a reference for the development of AI learning systems in the education sector.